Depth of neutrophil nadir after first cycle of R-CHOP predicts outcome in diffuse large B-cell lymphoma – a nationwide population-based cohort study. Issue 8 (3rd July 2019) - Clausen, Michael Roost; Ulrichsen, Sinna Pilgaard; Larsen, Thomas Stauffer; Poulsen, Christian B.; Tojaga, Selma; Pedersen, Per Trøllund; Madsen, Jakob; Pedersen, Robert Schou; Josefsson, Pär Lars; Gørløv, Jette Sønderskov; Nørgaard, Mette; d'Amore, Francesco
Abstract: We investigated if survival was predicted by nadir neutrophil counts after the first cycle of R-CHOP in patients with newly diagnosed diffuse large B-cell lymphoma (DLBCL). Neutrophil counts (10 9 /L) were categorized in four grades in the nadir time frame. Prognostic indices and comorbidity levels were calculated and used to adjust the Cox regression model. Kaplan–Meier and Cox regression methods were used to estimate and compare survival. We identified 965 patients. Grade 4 neutropenia was present in 432 (45%). Grade 0 patients had a 5-year overall survival of 67%, grade 1–2: 78%, grade 3: 64%, and grade 4: 57%. Compared with grade 0 adjusted hazard ratios (HR) for death were: 0.77 (95% CI 0.49–1.21) for grade 1–2, 1.18 (95% CI 0.82–1.71) for grade 3, and 1.33 (95% CI 1.02–1.73) for grade 4. Grade 4 neutropenia after the 1st cycle of chemotherapy predicted inferior outcome compared with grade 0 and 1–2. Grade 1–2 neutropenia seemed to have superior outcome.